Evaluation and Optimization for Extraction Parameters of Allium sativum Extract using Microwave Hydrodistillation (MHD) - Yeni Variyana; Mahfud Mahfud (CHEMICA: Jurnal Teknik Kimia, 2021)
Allium sativum L extraction using microwave hydrodistillation (MHD) was chosen as one of the techniques for becoming a safer and greener technology. The yield of garlic oil obtained by MHD using water as solvent. The optimization was designed by response surface methodology (RSM) to evaluate and analyze the effect parameters of raw material mass, microwave power, and extraction time. The highest yield was found in 100 g, 450 W, and 90 min of 0.1392% based on experimental data. In addition, RSM using the quadratic model predicted that optimal condition at 88.09 g, 474.94 W, and 99.53 min was 0.1430%, respectively. An ANOVA analysis resulted in a p-value of less than 0.05 with a high determination coefficient (R2 = 0.9971). It indicates that this model gives a significant response and has good accuracy. Furthermore, the error rates between experimental data and the predicted model were less than 5%. The model obtained from optimization is close to the reability runs and could be explained for correlating the yield of garlic oil with parameter conditions using optimization.